Pengaruh Kepemimpinan, Komitmen Kerja dan Disiplin Kerja terhadap OCB di Sekretariat Daerah Kabupaten Mandailing Natal - Ira Shanty Dalimunthe; Syamsir Syamsir; Erianjoni Erianjoni; Asnil Asnil (Journal of Education on Social Science (JESS), 2026)
Organizational Citizenship Behavior (OCB) plays a vital role in enhancing the quality of public services, productivity, and organizational effectiveness among State Civil Apparatus (ASN), as it supports the effective execution of duties and may extend beyond formally assigned job responsibilities. OCB contributes to the development of a harmonious work environment, strengthens employee engagement, enhances teamwork, and serves as an internal control mechanism that reduces the potential for fraudulent behavior within organizations. Accordingly, this study aims to examine the effects of leadership, work commitment, and discipline on OCB at the Regional Secretariat of Mandailing Natal Regency. This research employed a quantitative approach using a path analysis model to assess the relationships between independent variables and the dependent variable. Research were collected through observations, interviews, and questionnaires administered to employees of the Regional Secretariat of Mandailing Natal Regency. To ensure comprehensive results, a saturated sampling technique was utilized, encompassing the entire population of 83 employees. The results indicate that, simultaneously, the examined variables have a positive and significant effect on OCB; however, partial analysis reveals no significant individual effect on OCB. These findings suggest that other factors may influence the relationships between the independent variables and OCB.